Modeling and optimizing the evacuation of hospitals based on the MRCPSP with resource transfers - Jens Poppenborg (Elsevier, 2016)
In this paper, we consider the problem of hospital evacuation and model it as a multi-mode resource-constrained project scheduling problem (MRCPSP) with additional resource transfers and blockings. Based on this model two heuristic decomposition approaches are proposed. The first uses a tabu search algorithm for the mode assignment problem, the scheduling subproblem is solved by adapted serial and parallel schedule generation schemes using priority rules. The second is based on a decomposition into an evacuation and a routing subproblem where solutions are represented by resource flows. Computational experiments were performed for both approaches using randomly generated instances based on real-world scenarios.